Morocco : 2008 Article IV Consultation-Staff Report; Staff Statement; Public Information Notice; and Statement by the Executive Director for Morocco. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2008)
The 2008 Article IV Consultation discusses the economic growth for Morocco, which has made major progress to strengthen the economy's resilience to shocks. Sound macroeconomic policies combined with sustained structural reforms and the opportunities provided by globalization have resulted in a gradual improvement in living standards. Executive Directors considered that Morocco's universal subsidy scheme is the most important policy issue facing the authorities. They shared the authorities' assessment of the main upside risks to inflation, including possible second-round effects from higher imported prices and increased demand pressures.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet